Addition of curcumin to the diet of dairy sheep improves health, performance and milk quality - Jaguezeski A.M.* (2018)
© 2018 Elsevier B.V.The objective of this study was to evaluate whether the addition of curcumin to the diet of lactating ewes had positive effects on animal health, productive performance and milk quality. Eighteen Lacaune females were divided into two groups: control (group C) and treated (group T). Animals of group T received a diet supplemented with curcumin at 100 mg/kg feed for 15 d. On days 0, 10 and 15, samples of blood and milk were collected. The number of total blood leukocytes was lower on days 10 and 15, as a consequence of the reduction in the number of neutrophils and lymphocytes in group T (P < 0.05). Total serum protein levels were also lower due to decreased globulins (P < 0.05) in group T, as were levels of tumor necrosis factor alpha. Interleukin 10 levels were higher in group T animals (P < 0.05). Levels of reactive oxygen species were lower, but the activities of antioxidant enzymes (glutathione S-transferase, catalase and superoxide dismutase) increased significantly in the blood of group T ewes (P < 0.05). Milk yields increased in group T ewes (P < 0.05), and there was a reduction in somatic cell count and protein oxidation in their milk. Nevertheless, we observed an increase in ferric reducing ability of plasma in milk of group T (P < 0.05). We found that the unsaturated fatty acid oleic acid increased, and saturated fatty acid hexadecanoic acid decreased in milk of group T (P < 0.05). In general, a significant increase in levels of monounsaturated fatty acids was observed. We conclude that the addition of curcumin in sheep diet had antioxidant and anti-inflammatory effects, and that it improved productive performance and milk quality.